Two different domain architectures generate structural and functional diversity among bZIP genes in the Solanaceae family - Choi, Jin-Wook; Kim, Ha-Eun; Kim, Seungill (Frontiers in Plant Science, 2022)
The bZIP gene family is one of the largest transcription factor families and has important roles in plant growth, development, and stress responses. However, bZIP genes in the Solanaceae family have not been extensively investigated. Here, we conducted genome-wide re-annotation in nine Solanaceae species and Arabidopsis thaliana. We annotated 935 bZIP genes, including 107 (11%) that were newly identified. Structural analyses of bZIP genes in the Solanaceae family revealed that the bZIP domain displayed two types of architectures depending on the presence of an additional domain, suggesting that these architectures generate diversified structures and functions. Motif analyses indicated that the two types of bZIP genes had distinct sequences adjacent to the bZIP domain. Phylogenetic analyses suggested that the two types of bZIP genes distinctly evolved and ultimately adapted in different lineages. Transcriptome analyses in pepper (Capsicum annuum) and tomato (Solanum lycopersicum) revealed putative functional diversity between the two types of bZIP genes in response to various abiotic stresses. This study extensively updated bZIP gene family annotations and provided novel evolutionary and functional evidence for the role of bZIP genes in Solanaceae plants. Our findings provide evolutionary and functional characteristics of bZIP genes for a better understanding of their roles in Solanaceae plants.